Current Treatment Strategies for Acute Type B Aortic Dissection. (January 2015) - Mousa, Albeir Y.; Abu-Halimah, Shadi; Gill, Gurpreet; Yacoub, Michael; Stone, Patrick; Hass, Stephen; Campbell, John E.; AbuRahma, Ali F.
Acute type B aortic dissection (ATBAD) is a medical emergency that is a common occurrence in patients with atherosclerotic disease. The presentation is usually severe, with tearing pain that radiates to the back, and various levels of end-organ ischemia and malperfusion, even rupture, may occur. Everyone agrees that prompt and aggressive blood pressure control with β-blockers and nitroprusside is imperative, but when to surgically intervene is still not well characterized. However, the advent of minimally invasive stent graft placement has reshaped our thoughts regarding therapeutic intervention for ATBAD. This review is an attempt to define the current surgical indications for treating ATBAD.